IMPLEMENTASI PROGRAM PENJAMINAN POLIS ASURANSI DI INDONESIA - Widhiawati, Premita Fifi; Fuad, Fokky; Machmud, Aris (Lex Jurnalica, 2024)
Insurance is an important instrument that functions as a savior when someone experiences a disaster, whether in illness, accident, or even death. General insurance is a critical task, especially if it is related to covering disasters that occur in a business. Banking customers have a guarantee of a return of their savings or deposits at the bank's institution and insurance. Customers do not have a guarantee of a return of the premium they have paid for the policy they own. This research aims to study, understand, and analyze the implementation of the Policy Guarantee Program as mandated by the Insurance Law. The research is normative juridical with a statutory regulatory approach involving primary and secondary legal sources and theoretical studies used to analyze problems related to insurance and premium guarantees. The results show that the Government has not seriously handled the issue of policy guarantees because it still imposes this task on the LPS. At the same time, the duties and authority of the PPP are very urgent, and the PPP is an independent institution, as is done by other countries.Keywords: Insurance, Policy, Policy Guarantee Program.